Warren G. Child papers - Child, Warren G. (Warren Gerald), 1883-1938.
Diary (1920-1930) kept by Child while serving aboard seaplane tenders and aircraft carriers and as superintendent of the naval flight school, Pensacola, Fla.; and printed matter and photographs chiefly relating to naval aviation between World War I and World War II.
Naval officer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Naval Air Station Pensacola (Fla.); United States. -- Navy -- Aviation; Aircraft carriers -- United States; Flight training -- Florida -- Pensacola; Naval aviation -- United States; Seaplanes -- United States; Naval officers